Effect of Different Surface Treatments and Orthodontic Bracket Type on Shear Bond Strength of High-Translucent Zirconia: An In Vitro Study - Yasamin Babaee Hemmati; Hamid Neshandar Asli; Mehran Falahchai; Sina Safary (Hindawi Limited, 2022)
Objective. Considering the increasing number of adults seeking orthodontic treatment, and the possible need for bracket bonding to monolithic zirconia restorations, knowledge about the preferred type of bracket (metal/ceramic) and the most efficient surface treatment is imperative to achieve acceptable shear bond strength (SBS). This study aimed to assess the effect of different surface treatments and orthodontic bracket types on SBS of high-translucent zirconia. Materials and Methods. Totally, 248 disc-shaped zirconia specimens were assigned to two groups for bonding to metal and ceramic brackets. Each group was divided into four subgroups (n = 31) for the following surface treatments: no surface treatment (control group), airborne-particle abrasion (APA), tribochemical silica coating with CoJet, and CO2 laser irradiation. The mean surface roughness (Ra value) was measured. The SBS was measured after bracket bonding and thermocycling. Data were analyzed by two-way ANOVA, Tukey, Kruskal-Wallis, Mann-Whitney, and Fisher exact tests, and Bonferroni correction (α=0.05). Results. The mean Ra value was significantly different among the surface treatment subgroups (P<0.001). The APA and CoJet subgroups were not significantly different regarding Ra (P=0.754). All other pairwise comparisons yielded significant differences (P<0.001). Bracket type, surface treatment, and their interaction significantly affected the SBS (P<0.001). Ceramic brackets bonded to zirconia surfaces treated with CoJet yielded the maximum SBS while ceramic brackets bonded to control and lased surfaces resulted in minimum SBS. No significant difference was noted in the SBS of different surface treatment groups when metal brackets were used (P>0.05). Conclusions. The use of ceramic brackets and CoJet surface treatment would be the most appropriate combination to achieve optimal bonding to high-translucent zirconia restorations.